Microbial Root Mutualists Affect the Predators and Pathogens of Herbivores above Ground: Mechanisms, Magnitudes, and Missing Links - Tao, Leiling; Hunter, Mark D.; de Roode, Jacobus C. (Frontiers in Ecology and Evolution, 2017)
Tri-trophic interactions among plants, herbivores and natural enemies of herbivores are common in nature, and are crucial components of trophic cascades and the dynamics of community composition. Plant traits are key determinants of the interactions between herbivores and their natural enemies aboveground, which in turn are affected by soil organisms. Recent years have seen a surge in studies of the interactions between below- and aboveground biota, including descriptions of how microbial root mutualists influence plant traits and herbivore performance. However, concomitant effects on the natural enemies of herbivores remain relatively poorly understood. Here, we review the currently available literature to assess how and when mutualistic root microbes impose significant indirect effects on the performance of predators and pathogens of insect herbivores. We focus on how root microbes influence predator attraction, on-plant foraging efficiency, and the quality of prey tissues. We also consider the underappreciated effects of microbial root mutualists on the growth, transmission, and virulence of insect pathogens. We end by discussing missing links and important directions for future research.